1994
DOI: 10.1177/026835559400900111
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Long-Term Efficacy of Two Different Venoactive Drugs in Patients with Post-Thrombotic Syndrome

Abstract: Objective: In an open cross-over study, the effect of two different venoactive drugs was prospectively studied in a series of patients with post-thrombotic syndrome. Design: Prospective, open cross-over study. Patients: Twenty-nine patients with established unilateral deep venous insufficiency of at least 12 months duration, and a history of venography-proven deep venous thrombosis in the affected leg. Interventions: On entering the study, patients were randomly assigned to receive either Hidrosmina (Venosmil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…113 The drugs evaluated were rutosides (thought to reduce capillary filtration rate and microvascular permeability to proteins), defibrotide (downregulates plasminogen activator inhibitor-I release and upregulates prostacyclin, prostaglandin E2, and thrombomodulin), by guest on http://circ.ahajournals.org/ Downloaded from October 28, 2014 and hidrosmin (unknown mechanism of action). 114 The main features of these studies are shown in Table 9.…”
Section: Pharmacotherapy To Treat Ptsmentioning
confidence: 99%
See 2 more Smart Citations
“…113 The drugs evaluated were rutosides (thought to reduce capillary filtration rate and microvascular permeability to proteins), defibrotide (downregulates plasminogen activator inhibitor-I release and upregulates prostacyclin, prostaglandin E2, and thrombomodulin), by guest on http://circ.ahajournals.org/ Downloaded from October 28, 2014 and hidrosmin (unknown mechanism of action). 114 The main features of these studies are shown in Table 9.…”
Section: Pharmacotherapy To Treat Ptsmentioning
confidence: 99%
“…Monreal et al 113 showed that both hidrosmin and rutosides reduced symptoms but that hidrosmin produced greater improvement. Statistically significant improvement in pain and edema scores was observed by Coccheri et al 112 with defibrotide versus placebo, whereas claudication, skin pigmentation, and lipodermatosclerosis were unchanged.…”
Section: Pharmacotherapy To Treat Ptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venoactive drugs' mechanism of action is not entirely clear [96]. Rutosides are thought to reduce capillary permeability [97,98]; defibrotides downregulate plasminogen activator inhibitor-1 and upregulate prostaglandin, prostacyclin and thrombomodulin [99]; and flavonoids have a multi-faceted mechanism of action [100]. The micronized purified flavonoid fraction (MPFF) contains a combination of several flavonoids, and is thought to increase venous tone, reduce stasis, reduce venous wall inflammation and increase capillary permeability [101].…”
Section: What Medical Measures Should Be Used For Treatment Of Pts?mentioning
confidence: 99%
“…It has been shown that hidrosmin reduces the increase of vascular permeability induced by bradikinin, histamine and other mediators, and that it has a vitamin P-like activity (Quintana et al 1988). Moreover, hidrosmin increased human red blood cell deformability in-vitro (Iriarte et al 1988a) and ex-vivo (Iriarte et al 1988b), is used in the clinical management of chronic venous insuf®ciency (Boada et al 1992;Monreal et al 1994), and is effective in the prevention of the development of clinical symptoms of venous insuf®ciency after venous thrombosis (Monreal et al 1997).…”
mentioning
confidence: 99%